2022
DOI: 10.1021/acs.jpclett.2c01629
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanoelastic Glimpse on Hyaluronan-Coated Extracellular Vesicles

Abstract: Cancer cells secrete extracellular vesicles (EVs) covered with a carbohydrate polymer, hyaluronan (HA), linked to tumor malignancy. Herein, we have unravelled the contour lengths of HA on a single cancer cell-derived EV surface using single-molecule force spectroscopy (SMFS), which divulges the presence of low molecular weight HA (LMW-HA < 200 kDa). We also discovered that these LMW-HA-EVs are significantly more elastic than the normal cell-derived EVs. This intrinsic elasticity of cancer EVs could be directly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 48 publications
9
19
0
Order By: Relevance
“…Equilibrium snapshots of all the cases are shown in SI Figure S1, which are similar to those reported in the previous study 17 . The equilibration in each case is confirmed by the convergence of the area per lipid of the DPPC bilayer as done in our previous work 17 . The interface between HA-water and DPPC phases is computed from the equilibrium density profiles of the molecular constituents.…”
Section: Resultssupporting
confidence: 82%
“…Equilibrium snapshots of all the cases are shown in SI Figure S1, which are similar to those reported in the previous study 17 . The equilibration in each case is confirmed by the convergence of the area per lipid of the DPPC bilayer as done in our previous work 17 . The interface between HA-water and DPPC phases is computed from the equilibrium density profiles of the molecular constituents.…”
Section: Resultssupporting
confidence: 82%
“…Differential ultracentrifugation was performed to isolate EVs from breast cancer and normal epithelial breast cells (T47D and MCF10A). 15 Dynamic light scattering (DLS), FESEM imaging, zeta potential, and atomic force microscopy (AFM) were performed with isolated EV samples to determine EV dimensions and charge (Figure 1A, Figures S1 and S2, and Table S1). The data revealed that both EVs are spherical, and the diameters of cancer EVs are smaller (55 ± 15 nm) than those of normal EVs (100 ± 19 nm).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The issue of low and medium molecular weight HA being retained with some EV isolation protocols is further complicated by studies indicating that HA is a component of EVs obtained from synovial fluid (Mustonen et al, 2016(Mustonen et al, , 2022, mesothelial cells (Rilla et al, 2013) and cancer cells (Paul et al, 2022;Pendiuk Goncalves et al, 2023;Rilla et al, 2013). Specifically, studies have reported that HA is associated with the EV surface (Arasu et al, 2017;Pirri et al, 2022;Rilla et al, 2014).…”
Section:  Resultsmentioning
confidence: 99%